Consumer’s perceptions and buying intentions for furniture made from recycled wood slabs - Abdul Latif, Nur Hannani; Hamdan, Muhamad Haikal; Ahmad Zaki, Junaiza; Shafie, Amran; Awang @ Othman, Ahmad Fauzi; Kamarudin, Norashikin (Universiti Teknologi MARA (UiTM), 2024)
The rising cost of raw materials has redirected the furniture industry’s focus towards innovation and sustainability, emphasizing wood waste as a promising resource for furniture production. Activities such as sawmilling, wood machining, and furniture manufacturing generate wood waste, including slabs, offcuts, and shavings, which can reduce profit margins. Recycling this waste explores innovative methods to add value and minimize waste. Despite the growing interest in wood waste as potential furniture material, there is limited data on the acceptance of furniture made from it. This study aimed to analyze consumer perceptions and buy intentions for a coffee table made from recycled wood slabs. Wood slabs were chosen as the primary material due to their availability and aesthetic appeal, which can bring uniqueness to the product. After successfully developing the product, a closed-ended questionnaire survey was conducted with 100 randomly selected respondents from diverse demographic backgrounds (including gender, age, and monthly income). The survey aimed to collect feedback on product attributes such as material suitability, design preferences, and buying intentions using a five-point Likert scale. Findings revealed that the durability, unique appearance of the recycled wood slabs, and its environmental benefits influenced most consumers' preferences and buying interest, indicating a positive reception of this product among potential consumers. All respondents expressed satisfaction with the product’s attributes, with a mean rating above 4.0 indicating agreement. Respondents aged 31 to 40 show the highest interest (mean rating 4.5 and above) in the product attributes that demonstrate acceptance of recycled wood slabs as a potential material for furniture production. It can be concluded that this product holds high commercial potential in the current furniture market